IMPLEMENTATION OF QUALITY FUNCTION DEPLOYMENT (QFD) IN UD. PRODUCTION FURNITURE TO DESIGN SCANDINAVIAN STYLE WARDROBE PRODUCTS - Hanifah Juliyanti (Journal of Management and Islamic Finance, 2022)
The product is an important aspect for the company because it is what the company can produce for consumers. The products created by the company must meet consumers’ wants and needs. Therefore, consumer’s wants and needs are important aspects of the company that can be reviewed to improve product quality at the company. This study aims to determine the implementation of the Quality Function Deployment (QFD) method as a problem-solving solution in designing Scandinavian-style wardrobe products at UD. Furniture Production. This research was conducted using a quantitative method with a few qualitative methods to conduct a survey related to the voice of desire and consumer satisfaction. This data collection technique used interview methods and questionnaires. Meanwhile, the sampling technique used a non-probability sampling technique, namely consumers or customers from UD. Furniture Production.